Analysis of geoeconomic situation in Western Balkans - Sedlák, Michal; Lisa, Aleš, 1956-; Vymětal, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
Primary aim of this thesis is to analyze geoeconomic situation in Western Balkans region. First part of the thesis introduces theoretical concept of geoeconomics during its birth and how the theory has evolved until now. Another theoretical chapter addresses the region of Balkans, its complicated history, economy, and politics, and why it is so attractive for external players. There are three major active powers in the region and the analysis focus on their activities. Three of the Western Balkans countries are selected to better display the main points of the analysis. These countries are Serbia, Bosnia and Montenegro. And for further clarification the focus is narrowed down onto three sectors where geoeconomic activity is the most intense. These sectors are trade, investments and energy. Geoeconomic activity and tools of each great player in these three sectors is examined and compared to one another. Relevant findings are summarised and potential forecast for the development of the region is provided, with a possible evolution of each of the three powers’ activities.
Vedoucí práce: Aleš Lisa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses